The Impact of Employee Engagement and Ship Environment on Job Satisfaction and Employee Loyalty: Evidence from a Crew Manning Company in Indonesia - Goenadhi, Felix (Lentera Ilmu Madani, 2025)
This study investigates the determinants of employee loyalty in the maritime crew manning industry, focusing on employee engagement, ship environment, and job satisfaction. The maritime sector is characterized by demanding working conditions, extended periods away from home, and high operational risk, making employee retention a persistent managerial challenge. Using a quantitative approach, data were collected through a structured questionnaire distributed to crew members employed by a crew manning company in Indonesia. A total of 32 valid responses were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that the ship environment has a significant positive effect on job satisfaction, while employee engagement does not show a statistically significant relationship with job satisfaction. Furthermore, job satisfaction is found to have a significant positive influence on employee loyalty. These results indicate that, in a shipboard context, tangible and social working conditions play a more decisive role in shaping employee satisfaction and loyalty than psychological engagement alone. This study contributes to the literature on maritime human resource management by emphasizing the contextual specificity of engagement mechanisms and offers practical implications for crew manning agencies seeking to improve retention and operational stability.